2023
DOI: 10.2147/idr.s422564
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of Models for the Risk of Multi-Drug Resistant Bacteria Infection and Prognosis in Elderly Patients with Pulmonary Infection: A Multicenter Retrospective Study

Shu Wang,
Jing Li,
Jinghong Dai
et al.

Abstract: Purpose The aim of this study was to establish risk prediction and prognosis models for multidrug-resistant bacterial infections (MDRB) in elderly patients with pulmonary infections in a multicenter setting. Patients and Methods This study is a retrospective cohort analysis in Anhui province of China. Data dimension reduction and feature selection were performed using the lasso regression model. Multifactorial regression analysis to identify risk factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Results of this study are in line with other studies which showed that restriction of endotracheal intubation was associated with reduction of mortality and MDR bacterial infection. 23 , 24 This study showed that previous FLQ treatment was associated with FLQ resistance in P. aeruginosa strains afterward isolated. It also showed that patients who received endotracheal intubation had higher rates of FLQ resistance.…”
Section: Discussionmentioning
confidence: 87%
“…Results of this study are in line with other studies which showed that restriction of endotracheal intubation was associated with reduction of mortality and MDR bacterial infection. 23 , 24 This study showed that previous FLQ treatment was associated with FLQ resistance in P. aeruginosa strains afterward isolated. It also showed that patients who received endotracheal intubation had higher rates of FLQ resistance.…”
Section: Discussionmentioning
confidence: 87%